Online User Reviews as a Design Strategy for Global Communities: Contributions of the Open Device Labs Case - Godinho, Raquel Paiva; Espinosa, Ruth S. Contreras (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Grass-roots community movements related to design practices and open spaces have emerged to address different issues. This study is part of a comprehensive research, which aims to explain the Open Device Labs (ODLs) ecosystem. The ODLs are a grass-roots community movement that aims to democratize cross-platform tests and evaluation on real devices. As a global community with 152 laboratories located in 35 countries, online user reviews play an essential role in helping the long-term prospects of the movement. From the Design perspective, this paper aims to answer the question: what can be learned about the ODL ecosystem from online user reviews? To answer this research question, we conducted a qualitative inductive analysis of n=217 user reviews posted on the community website, from 65 labs located in 12 countries. The results and categories presented here are a key contribution to understanding the ODL ecosystem, and ultimately to other global service communities.